Comparative analysis of human respiratory syncytial virus evolutionary patterns during the COVID-19 pandemic and pre-pandemic periods - Guo, Chi-yu; Zhang, Yu; Zhang, Yu-yue; Zhao, Wei; Peng, Xiang-lei; Zheng, Yan-peng; Fu, Yuan-hui; Yu, Jie-mei; He, Jin-sheng (Frontiers in Microbiology, 2023)
The COVID-19 pandemic has resulted in the implementation of strict mitigation measures that have impacted the transmission dynamics of human respiratory syncytial virus (HRSV). The measures also have the potential to influence the evolutionary patterns of the virus. In this study, we conducted a comprehensive analysis comparing genomic variations and evolving characteristics of its neutralizing antigens, specifically F and G proteins, before and during the COVID-19 pandemic. Our findings showed that both HRSV A and B exhibited an overall chronological evolutionary pattern. For the sequences obtained during the pandemic period (2019-2022), we observed that the HRSV A distributed in A23 genotype, but formed into three subclusters; whereas the HRSV B sequences were relatively concentrated within genotype B6. Additionally, multiple positively selected sites were detected on F and G proteins but none were located at neutralizing antigenic sites of the F protein. Notably, amino acids within antigenic site III, IV, and V of F protein remained strictly conserved, while some substitutions occurred over time on antigenic site Ø, I, II and VIII; substitution S389P on antigenic site I of HRSV B occurred during the pandemic period with nearly 50% frequency. However, further analysis revealed no substitutions have altered the structural conformations of the antigenic sites, the vial antigenicity has not been changed. We inferred that the intensive public health interventions during the COVID-19 pandemic did not affect the evolutionary mode of HRSV.